# unfold

Every functional programmer loves *fold*. fold is universal and expressive. But *fold* has a secret twin brother named *unfold* which undoes what *fold* does. In this post, we will see what *unfold* is and how it is related to *fold*.

`unfoldr`

builds a list from a seed value while `foldr`

reduces a list to a summary value.

`unfoldr :: (b -> Maybe (a, b)) -> b -> [a]`

`unfoldr`

takes the element and returns `Nothing`

if it is done producing the list or returns `Just (a, b)`

, in which case, `a`

is a prepended to the list and `b`

is used as the next element in a recursive call.

For example, we can define `iterate`

as follows:

`iterate f == unfoldr (\x -> Just (x, f x))`

Another simple use of `unfoldr`

:

```
> unfoldr (\b -> if b == 0 then Nothing else Just (b, b-1)) 10
[10,9,8,7,6,5,4,3,2,1]
```

As the name suggests, *unfold* is the categorical dual of *fold*. (Maybe it should be *cofold* instead of *unfold*.) It means we can get the signature of `foldr`

by reversing the arrows of `unfoldr`

, and vice versa.

Let’s try this.

```
unfoldr :: (b -> Maybe (a, b)) -> (b -> [a])
foldr :: (Maybe (a, b) -> b) -> ([a] -> b)
```

Oops! It is not our beloved `foldr`

function whose signature is:

`foldr :: (a -> b -> b) -> b -> [a] -> b`

# Type isomorphisms

But don’t be disappointed! We can show that they represent the same thing by using type isomorphisms:

`(a → b → b) → b → ([a] → b)`

by a -> b -> c ~= (a, b) -> c

`((a, b) → b) → b → ([a] → b)`

by a ~= () -> a

`((a, b) → b) → (() -> b) → ([a] → b)`

by a -> b -> c ~= (a, b) -> c

`(((a, b) → b), (() -> b)) → ([a] → b)`

by ((a -> c), (b -> c)) ~= Either a b -> c

`((Either (a, b) ()) → b) → ([a] → b)`

by Either a () ~= Maybe a

`(Maybe (a, b) -> b) → ([a] → b)`

Now we can clearly see that *unfold* is the dual of *fold*. If you want to learn more on the relationship between *fold* and *unfold*, see Conal Elliott’s Folds and unfolds all around us.

# Implementation

Here’s an implementation of `unfoldr`

.

```
unfoldr :: (b -> Maybe (a, b)) -> (b -> [a])
unfoldr f b = case f b of
Just (a, b') -> a : unfoldr f b'
Nothing -> []
```